Long-term cardiac remodeling and Arrhythmias in Nonelite Marathon Runners - Wilhelm, M.; Roten, L.; Tanner, H.; Schmid, J. P.; Wilhelm, I.; Saner, H. (The American Journal of Cardiology, 2012)
Long-term endurance sports are associated with atrial remodeling and atrial arrhythmias. More importantly, high-level endurance training may promote right ventricular (RV) dysfunction and complex ventricular arrhythmias. We investigated the long-term consequences of marathon running on cardiac remodeling as a potential substrate for arrhythmias with a focus on the right heart. We invited runners of the 2010 Grand Prix of Bern, a 10-mile race. Of 873 marathon and nonmarathon runners who applied, 122 (61 women) entered the final analysis. Subjects were stratified according to former marathon participations: control group (nonmarathon runners, n = 34), group 1 (1 marathon to 5 marathons, mean 2.7, n = 46), and group 2 (=6 marathons, mean 12.8, n = 42). Mean age was 42 ± 7 years. Results were adjusted for gender, age, and lifetime training hours. Right and left atrial sizes increased with marathon participations. In group 2, right and left atrial enlargements were present in 60% and 74% of athletes, respectively. RV and left ventricular (LV) dimensions showed no differences among groups, and RV or LV dilatation was present in only 2.4% or 4.3% of marathon runners, respectively. In multiple linear regression analysis, marathon participation was an independent predictor of right and left atrial sizes but had no effect on RV and LV dimensions and function. Atrial and ventricular ectopic complexes during 24-hour Holter monitoring were low and equally distributed among groups. In conclusion, in nonelite athletes, marathon running was not associated with RV enlargement, dysfunction, or ventricular ectopy. Marathon running promoted biatrial remodeling.